The effects of using a police case information portal on victims of sexual violence - Karítas Lára Rafnkelsdóttir 1997- (2024)
Sexual violence is a serious event that can have profound consequences on victims. The police play an important role in victims’ experience with legal proceedings and distress regarding the crime. Furthermore, information provision from the police can impact victims’ experience with the police and legal proceedings. This current study explored the effects of increased provision of information from the police in the investigative process to victims of sexual violence through an online information portal developed by the National Commissioner of Iceland. Seven women between the ages of 19 and 42 took part in the study, who had reported sexual violence to the Reykjavík Metropolitan Police. A semi-structured interview guide was used with questions about participants' experience with reporting sexual violence to the police, with a focus on the provision of information. Thematic analysis was used to analyse the data from the interviews. Four themes were identified, “Advantages of the information portal”, “Disadvantages of the information portal”, “No usage of the information portal” and “Uncertainty”. Findings revealed that increased provision of information is important in reducing uncertainty and well-being in the investigation process. Increased access to information through an information portal had mostly a positive effect on the participants. However, the information portal itself needs further improvement, it did not meet the needs of participants, who wanted more information than they had access to in the portal. Further studies are needed to confirm the importance of the provision of information and study further use of the information portal after improvements.